A real-world pharmacovigilance study of omalizumab using disproportionality analysis in the FDA adverse drug events reporting system database - Yongfu Song; Zhuang Wang; Na Wang; Xiaofei Xie; Tieshi Zhu; Yongji Wang (Scientific Reports)
Abstract Omalizumab is a biologic agent used in the management of allergic conditions, including asthma and urticaria. Although the efficacy of omalizumab has been well established, its safety profile is primarily derived from clinical trials with limited sample sizes. To conduct a comprehensive evaluation of its safety in larger populations, this study conducted an extensive analysis of data sourced from the America Food and Drug Administration’s Adverse Event Reporting System (FAERS), with the aim of elucidating adverse drug events associated with omalizumab in real-world settings. We extracted reports of adverse events associated with omalizumab from the FAERS database covering the period from the first quarter of 2004 to the second quarter of 2024. We assessed the significance of the association between omalizumab and adverse events using four distinct methods of disproportionality analysis. Furthermore, we analyzed adverse events across gender and age subgroups. We identified a total of 49,456 adverse event reports linked to omalizumab and pinpointed 357 adverse events related to omalizumab within 27 system organ classes. These adverse events encompassed several commonly reported reactions documented in the product labeling, including anaphylactic reactions (ROR: 17.28, 95%CI:16.62–17.96) and asthma (ROR:19.24, 95%CI:18.74–19.76), alongside unlisted reactions such as asthmatic crisis (ROR: 47.3, 95%CI: 43–52.03), lower respiratory tract congestion (ROR: 35.68, 95%CI: 30.42–41.84). Furthermore, the results of our analysis indicated that omalizumab-related adverse events displayed significant gender and age disparities. The median time to onset for all documented adverse events was approximately 145 days, with a substantial proportion occurring after one year of treatment. This study not only offers a significant reference for optimizing the utilization of omalizumab, enhancing its efficacy while minimizing potential side effects, but also facilitates the safe application and broader implementation of omalizumab in clinical practice.